Chaste thinking : the rape of Lucretia and the birth of humanism - Jed, Stephanie H, 1953- (Theories of representation and difference., 1989)
"A strikingly original and provocative critical interpretation of the ideology of early Florentine humanism; or the reception and continued transmission of humanist ideology in the U.S. today ; and of a significant but neglected text on Lucretia by Coluccio Salutati ... - Margaret W. Ferguson (back cover)